The Efficacy and Safety of Ginkgo Terpene Lactone Preparations in the Treatment of Ischemic Stroke: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Zhao, Huan; Guo, Qiang; Li, Baoli; Shi, Min (Frontiers in Pharmacology, 2022)
Background: This meta-analysis aimed to assess the efficacy and safety of ginkgo terpene lactone preparations including ginkgo diterpene lactone meglumine injection, ginkgolide injection and ginkgolide B injection for ischemic stroke (IS). Methods: We searched the randomized controlled trials (RCTs) with publication date earlier than August 31, 2021 in Pubmed, China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Journals Database (VIP), Chinese Biomedical Literature Database (CBM), Wanfang Database, Embase, and the Cochrane Library. RevMan 5.3 software was applied to analyze the data and generate forest plot and funnel plot. Meanwhile, publication bias was also assessed by Egger's test with STATA 12 software. Results: A total of 28 RCTs were eligible for inclusion. Among them, 23 RCTs were used to evaluate the efficacy of ginkgo terpene lactone preparations as the main treatment intervention for IS. To specific, ginkgo diterpene lactone meglumine injection was superior to control drug in improving clinical efficacy [RR=1.18, 95% CI (1.12, 1.24), Z=6.36, P<0.001] and neurological function [MD=-1.42, 95% CI (-1.91, -0.93), Z=5.66, P<0.001]. However, the effectiveness of ginkgolide B injection group was equivalent to the control group. Additionally, ginkgolide injection achieved better clinical efficacy [RR=1.10, 95% CI (1.02, 1.18), Z=2.36, P=0.02], but the changes of neurological function deficit was not obviously different between two groups [MD=-0.43, 95% CI (-4.32, 3.46), Z=0.22, P=0.83]. Furthermore, meta-analysis of 5 trials on ginkgo diterpene lactone meglumine injection combined with recombinant tissue plasminogen activator (rt-PA) thrombolytic therapy for acute IS showed that combination therapy was better in improving clinical efficacy [OR=1.91, 95% CI (1.13, 3.22), Z=2.41, P=0.02] and neurological function [MD=-3.31, 95% Cl (-3.64,-2.98), Z=19.63, P<0.001]. Importantly, no serious adverse drug reactions/adverse drug events (ADRs/ADEs) were reported. Conclusions: Ginkgo terpene lactone preparations have good therapeutic effects on patients with IS. For acute IS, ginkgo diterpene lactone meglumine injection can be used as a complementary therapy to improve the clinical efficacy of rt-PA.